Two case reports of severe myocarditis associated with the initiation of dolutegravir treatment in HIV patients. Issue 47 (November 2016) - Mahlab-Guri, Keren; Asher, Ilan; Rosenberg-Bezalel, Shira; Elbirt, Daniel; Burke, Michael; Sthoeger, Zev M.
Abstract: Rationale: The integrase inhibitor dolutegravir is now recommended as first-line treatment for HIV. A single case of myocarditis after treatment with dolutegravir was reported in the FLAMINGO trial. We present here 2 cases of severe myocarditis that occurred shortly after the initiation of dolutegravir treatment. Patients concerns: The first case is a 45-year-old female who developed severe congestive heart failure and died, weeks after the initiation of dolutegravir treatment (for simplification of her antiretroviral regimen). The second case was a 51-year-old male who presented with effort dyspnea 3 weeks after the initiation of dolutegravir treatment and was later diagnosed as severe congestive heart failure. The treatment was changed and the patient survived, but he still suffers from severe heart failure with functional impairment. Diagnosis and Outcome: Patient 1 died, patient 2 suffers from severe heart failure. Lessons: We discuss here the possible relationship between the initiation of dolutegravir treatment and the development of lymphocytic myocarditis in our patients, and we suggest a possible mechanism.